O Papel desempenhado pela acompanhante e sua adaptação ao ambiente hospitalar : estudo fundamentado no modelo de Roy - Santos, Maria Lígia de Oliveira dos (1999)
This is an exploratory, descritive research, it adopted as giiideline the two first phases of Adaptation Model of Roy, respecting the precepts of each mode(physiologic, self-concept, role7s function and interdependence). This had as objectives: evaluate the behaviours presented by companions during their pennanence ín hospital environment and identify stimulus that contribute to the acting of altered role in each adaptative mode, with emphasis in its inter-relation. Collecting data, it used the direct observation and semi-structured mterview on five companions, during june-july months at 1998 year, in the Units I and II, at Insíituíe Dr, José Frota, localizeded at Fortaleza Municipal. That one is considered as reference hospital to the whole Ceará State. The results, in physiologic mode, registered in the categories activity and resíing and nourishment. In self-concept mode revealed the self-concept altered, self-ideal ethícal and moral. In the role7s function mode, it identified as primary role in the sampler that the five companions of female Sex were between 18 and 40 years old belonging to the development phase of young adult to gerative adult. Conceming the secundary role, it related mothers, daughter, sisters, wife. It observed that in the tertiary role, the companions executed this role three or more times. In the interdependence mode, it detected that the other significative ofthe companion corresponds to the male companion, daughter and friend.Relating to the adaptative modes they revealed focal, contextual and residual stimulus. Regarding the inter-relation of adaptative modes, it identifíed uneffective stimulus that need nursing intervention on the four adaptative modes(physiologic, role function, self-concept and interdependence). When it is observed the modes, it perceives that the physiologic, affective, psychic and social integrity of companions of intemed patient are altered, on the sampler, evidencied by problems in the four modes, damaging the executiou of this role. The investigation results show that the companion’s role is altered(in role function), due the inappropriate place to the companion7 s permanence(in physiologic mode) and the existance of normatization takes the person to feel the selfvalour decreased, without liberty to act(in self-concept), so, increasing his potential to the impotence. They still revealed exist an abyss betwwen the companion and the supporfs system, the health’s professional( in the interdependence). It believes, that altered these stimulus, the companion can adapt, recovermg the security, decreasing the anxiety, the fears and, thus, increasing the self-esteem. It can be used , by the nurse in his intervention, as positive contextual stimulus, propitiating a recuperation more rigid of patienfs health.